Moral Leadership and Unethical Pro-organizational Behavior: A Moderated Mediation Model - Wang, Yujuan; Li, Hai (Frontiers in Psychology, 2019)
In this paper, we aim to examine the indirect effects of moral leadership on unethical pro-organizational behavior (UPB). Drawing on Social Identity Theory, identification with supervisors (social identity) and taking responsibility (personal identity) were hypothesized as mediators linking moral leadership and UPB. In addition, we aim to investigate the moderating role of moral courage in the relationship between moral leadership and UPB. We conducted two studies with two distinct samples: one on a sample of 161 MBA students, and the other on a sample of 205 enterprise employees in China. Data were collected through a self-reported questionnaire based on a two-wave research design and analyzed through Structural Equation Modeling. Results showed that moral leadership increased UPB through promoting identification with supervisors while reducing UPB via increasing taking responsibility. Additionally, the results also showed that moral courage moderated the mediating effects of identification with supervisors and taking responsibility upon the relationship between moral leadership and UPB. We contribute to the literature by demonstrating that moral leadership exerts its paradoxical effects on UPB indirectly through its impact on identification with supervisors and taking responsibility and therefore offers a better understanding of how and when moral leadership influences UPB. A number of managerial implications are also discussed.